A low-cost personal dosemeter based on optically stimulated luminescence (OSL) of common household salt (NaCl). (February 2016) - Ekendahl, Daniela; Bulánek, Boris; Judas, Libor
Abstract: Salt represents a radiation sensitive material that can be used for dosimetry. The objective of this experimental study was to test a low-cost salt dosemeter that was designed for personnel that are not radiation workers, but can operate in low probability events resulting in a serious external radiation exposure. The dosemeter is based on use of optically stimulated luminescence (OSL) of a common household salt. Attention was concentrated on its energy and angular responses. The dosemeter was fixed to the ICRU slab phantom and irradiated by photons of reference radiation qualities (ISO 4037-1) with mean energies between 33 and 1250 keV. Angular response was investigated for angles of incidence from 0° to 80° for radiation qualities of N-150 (∼118 keV) and S-Cs (∼662 keV). Single-Aliquot Regenerative-dose analytical protocol was employed for dose reconstruction. The results were evaluated with respect to Hp (10) measurement. The salt dosemeter can provide reliable or reasonably conservative Hp (10) estimates in radiation fields where photon energies > 100 keV predominate, radiation incidence angles are from 0° to 80° and also for rotational geometry. Furthermore, a personal dose reconstruction trial was demonstrated. Relative deviation between the measured and reference Hp (10) values was 5.5%. A practical disadvantage of the method is the more demanding analytical protocol. Highlights: Common salt has a considerable potential for dosimetry based on use of OSL. A simple salt personal dosemeter was designed and tested. Photon energy and angular responses were satisfactory for purposes of accidental dosimetry. Dose reconstruction trial proved the potential for reliable estimate of personal doses.